Aplikasi Money Manager sebagai Technology-Enhanced Learning Tool dalam Pembelajaran Ekonomi Digital: Studi Kasus Perubahan Perilaku Kedisiplinan Keuangan Mahasiswa - Wahyuni, Sri; Ulfah, Fadilla; Siregar, Dwi Rayana; Supriadi, Sudawan; Sri Susanti, Roza (Jurnal Pendidikan Ekonomi, 2025)
This qualitative case study research aims to analyze the mechanism and effectiveness of the Money Manager Application as a Technology-Enhanced Learning Tool (T-E Learning Tool) in fostering Financial Discipline among 6 students of the Economics Education Study Program at Jambi University, emphasizing its relevance within Digital-Based Economics Learning. The research procedure involved three phases: Pre Intervention, 14-day Intervention, and Post Intervention. Data were collected primarily through in-depth interviews and observational documentation, and subsequently analyzed using Descriptive Content Analysis to identify narrative findings. The results indicate that the Money Manager Application effectively overcame student behavioral barriers (such as laziness and inconvenience) and served as a practical learning tool that facilitated the comprehension of financial management concepts. The key finding resides in the mechanism of Instant Visual Feedback provided by the application; this feature triggered self-evaluation and accountability, thus significantly improving students' control and allocation of financial resources. It is concluded that this digital application is a powerful catalyst in achieving the goals of Digital-Based Economics Learning concerning Financial Discipline formation. Formal integration of similar digital tools into the curriculum is recommended, along with necessary technical improvements and minimization of disruptions (advertisements) to maximize its pedagogical potential.